Penyusunan Laporan Keuangan Berbasis Microsoft Excel Sesuai SAK EP dan ISAK 335 Pada Masjid Jami' Al Muhajirin Tangerang - Muhammad Raihan Nur Ma'ruf Raihan; Hafifah Nasution; Putri Haryani (LPPM Universitas Negeri Jakarta, 2026)
This project focuses on developing a Microsoft Excel-based financial reporting template for Masjid Jami’ Al Muhajirin Tangerang by referring to SAK EP and ISAK 335. The development process adopted the FAST model, while the existing problems were examined through the PIECES framework. The required information was collected from interviews, field observations, and supporting documents, such as the mosque’s 2025 financial records, fixed asset data, and organizational structure. The output of this project is an integrated Excel template that supports master data management, transaction entry, fixed asset recording, supporting schedules, and the preparation of financial reports. The reports generated include comprehensive income, changes in net assets, financial position, cash flows, and notes to the financial statements. In addition, a user guide was prepared to support the Treasurer, Secretary, and Head of DKM in using the template independently, allowing the mosque’s financial administration to continue consistently even when management changes occur.